Effects of Inorganic and Nano Copper Supplementation on Growth Performance, Nutrient Utilization and Mineral Availability in Growing Sahiwal Heifers - Kushwaha, Raju; Kumar, Vinod; Kumar, Muneendra; Vaswani, Shalini; Kumar, Avinash (Indian Journal of Animal Nutrition, 2022)
This study was conducted to evaluate the effect of inorganic and nano copper supplementation on feed intake, nutrient utilization, growth performance and mineral availability in growing Sahiwal heifers. Twenty four growing Sahiwal heifers were randomly allocated into four groups having six heifers in each groups and fed for 120 days. Feeding regimen was similar in all the groups except that treatment groups were supplemented with 0.0 mg copper, 10.0 mg inorganic copper, 5.0 and 10.0 mg of nano copper per kg dry matter (DM; ppm) in four respective groups. Nutrients requirement of experimental heifers were met by feeding concentrate mixture, berseem and wheat straw as basal diet. Group fed on basal diet supplemented with 0.0 mg copper/kg DM served as a control. Experimental heifers were monitored daily for DM intake (DMI) and fortnightly body weight change. At the end of the study, a digestion trial of 7 days was conducted to study the effect of inorganic and nano copper supplementation on nutrients utilization. Feed intake, nutrient digestibility and growth performance were similar in all experimental groups fed on basal diet with or without supplemental Cu. Dietary supplementation of inorganic Cu and nano Cu did not exert any effect on absorption of Ca, P, Zn and Fe in different groups. Although, absorption of Cu in nano Cu supplemented groups were higher (P<0.05) than other groups. Finally, it was concluded that level of 5 ppm nano Cu can be selected for feeding in growing cattle as it exerts similar effects as showed by 10 ppm inorganic Cu.